How Location Efficient Is LIHTC? Measuring and Explaining State-Level Achievement. Issue 3 (4th May 2017) - Adkins, Arlie; Sanderford, Andrew; Pivo, Gary
Abstract: A growing recognition that the cost of transportation should be included in calculations of housing affordability has led to efforts to promote location efficiency (LE) in affordable housing policy. Because the program is responsible for most new affordable housing in the United States, the Low Income Housing Tax Credit (LIHTC) program has the potential to be a link between housing affordability and LE. This research analyzes the extent to which LIHTC units built between 2007 and 2011 were in location-efficient places. Ordinary least squares regression analysis was used to test the role of market, policy, developer, and urban form factors in determining state-level LIHTC LE. We find that for the nation as a whole, from a quarter to half of LIHTC units added during this period were in location-efficient places, depending on the LE criteria applied. State-by-state comparisons showed wide variation in both our absolute measures of LIHTC LE and our relative measures of LIHTC LE compared with overall housing in each state. State policy and nonprofit developers were associated with higher LIHTC LE and had a positive effect on a state's ability to outperform its underlying urban form.